The next great Jane - Going, K. L. (Kelly L.) (Dial Books for Young Readers, 2020)
Twelve-year-old Jane Brannen wants nothing more than to be a successful author like Jane Austen. She gets a chance to meet a famous author when romance novelist J.E. Fairfax comes into town, and her stay is extended because of a terrible hurricane. However, the storm also causes her mother and her fiancee to arrive and file for full custody of Jane. Jane doesn't want to move to California with them and schemes to find a way to stay with her father in Maine.